Approaches to Prognosing the European Economic Crisis Through a New Economic–Financial Risk Sensitivity Model - Monica Laura Zlati; Costinela Fortea; Alina Meca; Valentin Marian Antohi (Economies)
This paper presents a novel approach to prognosing European economic crises through the development of an economic–financial risk sensitivity model. The model integrates key macroeconomic indicators such as government deficit (NETGDP), GINI coefficient, social protection expenditure (ExSocP), unemployment rate (UNE), research and development spending (RDGDP), and tax structures (TXSwoSC), assessing their role in predicting economic vulnerability across European countries. By applying the Kruskal–Wallis non-parametric test on data from 324 observations across multiple countries, significant differences were identified in the distribution of these variables. The results show that government policies related to social protection, R&D, and taxation play an important role in a country’s resilience to economic shocks. On the other hand, indicators such as income inequality and unemployment exhibit less variation, reflecting global economic conditions. The model provides a comprehensive risk assessment framework, allowing for the early detection of potential economic crises and guiding policy adjustments to mitigate risks. This methodology offers valuable insights into the sensitivity of European economies to financial disruptions, emphasizing the importance of fiscal policies and social expenditure in maintaining economic stability.